Review of Ability Level of Physical Condition of West Sumatra Water Polo Athletes - Jumedi, Jumedi; Rijal, Muhammad Zul; Syaiful, Syaiful (Yayasan Sekora, 2019)
The problem in this study is the alleged low level of the physical condition of the athletes in West Sumatra water polo. This research is a descriptive study, which aims to determine the level of ability of the athletes' physical condition West Sumatra water polo. The sampling technique was carried out by total sampling, where the entire population of all male athletes of the West Sumatra Water Polo who were still actively practicing in the Padang lotus swimming pool aged 20-27 years with a total of 20 people were sampled. Data were collected by means of tests and measurements on each element of the athlete's physical condition. Aerobic endurance is measured by a bleep test, leg muscle power is measured by a vertical power jump test, arm muscle power is measured by two hand medicine ball-push, speed is measured by a 30-meter sprint test, shuttle run agility (4x5 meters) , and eye-hand coordination was measured by a wall pass test. Data analysis was performed using descriptive analysis techniques through statistics (frequency tabulation). From the data analysis, it can be concluded that the best level of physical condition ability of West Sumatra water polo athletes is eye-hand coordination. Meanwhile, the lowest level of physical condition for water polo athletes in West Sumatra is agility. Therefore, the ability to be in physical condition needs to be improved through well-programmed training.